Assessment of the physical and combustion properties of briquettes produced from banana tree waste - Yadav, Yasha; Neupane, Sudan (Journal of Innovations in Engineering Education, 2021)
Nepal has an abundance of biomass resources. Heavy dependence on traditional source and waste management resulting from agricultural waste is one of the major problem in our country. Briquetting from agricultural waste can be an option for resource management. This study was undertaken to investigate the physical and combustion properties of briquettes produced from dried banana tree waste (leaves + pseudostem). Altogether four types of briquettes were produced, two from uncharred biomass using screw extruder and hydraulic jack briquetting machine and other two briquettes were produced from uncharred biomass/charcoal using screw extruder and beehive briquetting machine. For charred briquette, the density of screw extruder briquette (1.06 g/cm3) was higher than hydraulic briquette (0.33 g/cm3). For uncharred briquette, the density was higher (0.72 g/cm3) for screw extruder than beehive briquette (0.44 g/cm3). The Moisture content of briquettes varied from 7.23 to 11.04%, Volatile matter varied from 11 to 68.74%, Ash content varied from 4.94 to 49.43% and fixed carbon content varied from 15.27 to 32.34%. The calorific values of the briquettes ranged from 2462.0827 - 3899.193 kcal/kg, while the thermal efficiency ranges between 24.02– 30.71%, other results shows that the average burning rate between 3.55 and 6.41 g/min. Screw extruder briquette from uncharred Banana tree waste and beehive from charred/carbonized banana tree waste biomass was found to be comparatively better from the present study.